2010
DOI: 10.1111/j.1464-410x.2009.08835.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the incidence of uretero‐intestinal anastomotic stricture increased in patients undergoing radical cystectomy with previous pelvic radiation?

Abstract: Study Type – Therapy (case series)
Level of Evidence 4 OBJECTIVE To present our long‐term experience comparing uretero‐intestinal anastomotic (UIA) stricture rates after radical cystectomy (RC) in patients with and without previous pelvic radiotherapy (pRT), as the risk of stricture is thought to be higher in patients undergoing RC and urinary diversion (UD) with a history of pRT. PATIENTS AND METHODS We retrospectively analysed patients who had RC and UD between 1992 and 2008 by one surgical team. Patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 22 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…While earlier publications evaluating urinary diversion in the setting of prior radiation therapy advocated the use of transverse colon, 19 several contemporary series have shown the use of small bowel in selected patients to be safe and effective. 20,21 Notably only 1 complication in our series could be attributable to the bowel segment in particular, that of an enteric anastomotic leak (Clavien IIIb). Given the limited series presented, conclusions regarding the safety of a small bowel urinary diversion in patients with prior radiation therapy cannot be drawn.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…While earlier publications evaluating urinary diversion in the setting of prior radiation therapy advocated the use of transverse colon, 19 several contemporary series have shown the use of small bowel in selected patients to be safe and effective. 20,21 Notably only 1 complication in our series could be attributable to the bowel segment in particular, that of an enteric anastomotic leak (Clavien IIIb). Given the limited series presented, conclusions regarding the safety of a small bowel urinary diversion in patients with prior radiation therapy cannot be drawn.…”
Section: Discussionmentioning
confidence: 72%
“…Severe (Clavien grade III to V) complications were noted in 42% of patients (8 of 19) and the 90-day mortality rate in this cohort was 16% (3 of 19). With a median postoperative followup of 13 months (IQR 4,21), the 1 and 3-year overall survival was 84% and 52%, respectively. Conclusions: Cystectomy for hemorrhagic cystitis is associated with a high risk of perioperative complications and mortality, consistent with the baseline clinical status of this patient cohort and, as such, should remain a last resort to control bleeding after failure of conservative measures.…”
mentioning
confidence: 98%
“…Knap et al 16 reported that the risk of ureteroenteric strictures was significantly higher in patients with a history of pelvic radiotherapy than in those without. This associ ation, however, has not been supported by larger studies 4,8,13,17,20,21 , although a reduced success rate of stricture repair has been reported in patients with a history of pelvic radiotherapy 22 . This evidence highlights the importance of choosing a viable segment of ileum outside the confines of the irradiated field 19 .…”
Section: Risk Factors Patient-specific Risk Factorsmentioning
confidence: 95%
“…Anderson et al 1 noted that stricture rates are often under-reported owing to variable follow-up durations and nonstandardized use and frequency of urinary tract imaging. The majority of strictures occur within 2 years of surgery, with median time to diagnosis in the literature reported as 7-25 months after surgery 7,8,[11][12][13] , although they can occur as late as 160 months postoperatively 14 .…”
Section: Incidencementioning
confidence: 99%
“…3 The published rate of uretero-ileal anastomotic stricture after urinary diversion in the literature varies from 1.3-13%. [4][5][6][7][8][9][10] Though exact reasons for the development of uretero-ileal anastomotic stricture remain to be elucidated, it is thought to be due to an inflammatory or ischemic etiology. 6 It has been proposed that in most, the cause is likely multifactorial.…”
Section: Introductionmentioning
confidence: 99%